Immunometabolism pathways as the basis for innovative anti-viral strategies (INITIATE): A Marie Sklodowska-Curie innovative training network - Bowie, Andrew; O'Neill, Luke (My University, 2020)
The past century has witnessed major advances in the control of many infectious diseases, yet outbreaks and epidemics caused by (re-) emerging RNA viruses continue to pose a global threat to human health. As illustrated by the global COVID19 pandemic, high healthcare costs, economic disruption and loss of productivity reinforce the unmet medical need to develop new antiviral strategies to combat not only the current pandemic but also future viral outbreaks. Pivotal for effective anti-viral defense is the innate immune system, a first line host response that senses and responds to virus infection. While molecular details of the innate immune response are well characterized, this research field is now being revolutionized with the recognition that cell metabolism has a major impact on the antiviral and inflammatory responses to virus infections. A detailed understanding of the role of metabolic regulation with respect to antiviral and inflammatory responses, together with knowledge of the strategies used by viruses to exploit immunometabolic pathways, will ultimately change our understanding and treatment of pathogenic viral diseases. INITIATE is a Marie Sklodowska-Curie Actions Innovative Training Network (MSCA-ITN), with the goal to train 15 early stage PhD researchers (ESRs) to become experts in antiviral immunometabolism (https://initiate-itn.eu/). To this end, INITIATE brings together a highly complementary international team of academic and corporate leaders from 7 European countries, with outstanding track records in the historically distinct research fields of virology, immunology and metabolism. The ESRs of INITIATE are trained in these interdisciplinary research fields through individual investigator-driven research projects, specialized scientific training events, workshops on academia-industry interactions, outreach & communication. INITIATE will deliver a new generation of creative and entrepreneurial researchers who will be able to face the inevitable future challenges in combating viral diseases.
Keywords: Virology; Innate Immunity; Immunometabolism; Coronavirus; Influenza virus; Pneumovirus; Innovative training network